Explicit L2 inequalities for parabolic and pseudoparabolic equations with Neumann boundary conditions - J. R. Kuttler; V. G. Sigillito (International Journal of Mathematics and Mathematical Sciences)
Explicit L2 inequalities are derived for second and third order diffusion equations with Neumann boundary conditions. Such inequalities are useful in approximating solutions to partial differential equations by the method of a priori inequalities.